Right ventricular dysfunction predicts outcome after transcatheter mitral valve repair for primary mitral valve regurgitation. (15th September 2022) - Doldi, Philipp M.; Stolz, Lukas; Kalbacher, Daniel; Köll, Benedikt; Geyer, Martin; Ludwig, Sebastian; Orban, Mathias; Braun, Daniel; Weckbach, Ludwig T.; Stocker, Thomas J.; Näbauer, Michael; Higuchi, Satoshi; et al.
Abstract: Aims: Right ventricular dysfunction (RVD), as expressed by right ventricular to pulmonary artery coupling, has recently been identified as a strong outcome predictor in patients undergoing mitral valve edge‐to‐edge repair (M‐TEER) for secondary mitral regurgitation (MR). The aim of this study was to define RVD in patients undergoing M‐TEER for primary MR (PMR) and to evaluate its impact on procedural MR reduction, symptomatic development and 2‐year all‐cause mortality. Methods and results: This multicentre study included patients undergoing M‐TEER for symptomatic PMR at nine international centres. The study cohort was divided into a derivation (DC) and validation cohort (VC) for calculation and validation of the best discriminatory value for RVD. A total of 648 PMR patients were included in the study. DC and VC were comparable regarding procedural success and outcomes at follow‐up. Sensitivity analysis identified RVD as an independent predictor for 2‐year mortality in the DC (hazard ratio [HR] 2.37, 95% confidence interval [CI] 1.47–3.81, p  < 0.001), which was confirmed in the VC (HR 2.06, 95% CI 1.36–3.13, p  < 0.001). Procedural success (MR ≤2+) and symptomatic improvement at follow‐up (New York Heart Association [NYHA] class ≤II) were lower in PMR patients with RVD (MR ≤2+: 82% vs. 93%, p  = 0.002; NYHA class ≤II: 57.3% vs. 66.5%, p  = 0.09 for with vs. without RVD). In all PMR patients, the presence of RVD significantly impaired 2‐year survival after M‐TEER (HR 2.23, 95% CI 1.63–3.05, p  < 0.001). Conclusions: Mitral valve edge‐to‐edge repair is an effective treatment option for PMR patients. The presence of RVD is associated with less MR reduction, less symptomatic improvement and increased 2‐year mortality. Accordingly, RVD might be included into pre‐procedural prognostic considerations. Abstract : RVD predicts outcome after M‐TEER for PMR. CI, confidence interval; HR, hazard ratio; PMR, primary mitral regurgitation; RVD, right ventricular dysfunction.